Uncovering climate and human signals in near-millennium annual fire chronology for Norrbotten county, Northern Sweden - Jabłońska, Agnieszka (2021)
Forest fire is one of the major factors driving the dynamics of the boreal forest. Climate has the most significant contribution in shaping the fire occurrence, its spatial extent and severity. Anthropogenic activities have contributed to variation in fire activity, although the timing and the scale of the human impact are still heavily debated. Millennia-long annual records, which can inform us on the interplay of climate and human influences on fire activity in a long-term perspective, are largely missing for European boreal forests. To address this knowledge gap, I developed a dendrochronological reconstruction of fire activity using fire-scarred dead and live Scots pine trees in Norrbotten county, northern Sweden. Site reconstructions (n = 24) extended from 900-1200 AD to the present time. To assess the degree of climatic forcing upon fire activity, I conducted superposed epoch analysis using the ten largest fire years and Old World Drought Atlas. Fire occurrence varied significantly with time, with the most extensive fire years occurring during the drier-than-average conditions. Analysis of fire activity with the human population data extending to the mid-1500s suggested a negative correlation between the two factors.